Hormonal and plasma volume changes after presyncope - Hinghofer-Szalkay, Helmut; Lackner, Helmut K.; Rössler, Andreas; Narath, Bettina; Jantscher, Andreas; Goswami, Nandu (European journal of clinical investigation, 2011)
Eur J Clin Invest 2011; 41 (11): 1180–1185 Background  Aim of this study was to test the hypothesis that after presyncope, some blood hormone pools increase while others decrease. Materials and methods  In twelve healthy male adults, we determined plasma volume changes with plasma mass densitometry and hormone levels. The following were compared: supine rest, presyncope and 20‐min post‐presyncopal supine rest. We determined plasma renin activity (PRA), aldosterone, adrenocorticotropic hormone (ACTH), adrenomedullin and vasopressin (AVP) from venous blood samples. Results  Using passive 4‐min 70° head‐up tilt followed by 4‐min sequences of additional lower body negative pressure of increasing intensity (15 mmHg steps), presyncope occurred after 11·6 ± 2·8 min, at which time plasma volume was reduced by 15·5 ± 7·4%, aldosterone increased by 37%, ACTH by 75%, PRA by 187% and AVP about 16‐fold in average (all P < 0·01); no significant changes in adrenomedullin were seen. Twenty‐min post‐presyncope, ACTH increased above presyncopal levels (+36%, P < 0·05), aldosterone by 35% (P = 0·07). PRA (−47%, P < 0·01) and AVP (−84%, P < 0·05) decreased below presyncopal but were still above supine control (P < 0·01); similarly, plasma density fell by 2·17 ± 0·97 g L−1 below presyncopal (P < 0·01), but above supine control (P < 0·05), indicating rapid recovery (83% of initial plasma volume). Conclusions  We conclude that during the 20‐min supine post‐syncopal period, plasma volume, PRA and AVP return closer to baseline but aldosterone and ACTH continue increasing. The magnitude of observed concentration changes cannot be explained by haemoconcentration/haemodilution, rather it appears that the observed changes are indicative of hormone‐specific endocrine activation patterns in the recovery phase.